Mitigating the effect of persistent postnatal depression on child outcomes through an intervention to treat depression and improve parenting: a randomised controlled trial. (February 2018) - Stein, Alan; Netsi, Elena; Lawrence, Peter J; Granger, Charlotte; Kempton, Claire; Craske, Michelle G; Nickless, Alecia; Mollison, Jill; Stewart, D Anne; Rapa, Elizabeth; West, Valerie; Scerif, Gaia; et al.
Summary: Background: Maternal postnatal depression occurs following 10–15% of births and is associated with a range of negative child outcomes. Risks to children are particularly increased when postnatal depression is persistent. We aimed to examine whether a parenting video-feedback therapy (VFT) intervention versus a control treatment of progressive muscle relaxation (PMR), both added to cognitive behavioural therapy (CBT) for persistent postnatal depression, would lead to improved child outcomes at age 2 years. Methods: In this two-arm, parallel-design, individually randomised controlled trial, we recruited a community sample of women aged 18 years or older living within 50 miles of Oxford, UK, between 4·5 and 9·0 months post partum. All participants met diagnostic criteria for current major depressive disorder that had persisted for at least 3 months and had infants at 35 or more weeks of gestation, with a birthweight of 2000 g or greater, and without serious neonatal complications. Through a centralised service, women were randomly assigned by use of a minimisation algorithm, to receive either VFT or PMR, balanced for child sex, temperament, age, socioeconomic status, and severity of depression. Both groups also received CBT for depression. Primary outcomes were child cognitive development, language development, behaviour problems, and attachment security at age 2 years. There were 11 home-based treatment sessions before child age 1 year, followed by two booster sessions in the second year. Assessors were masked to treatment group allocation. All analyses were done according to the intention-to-treat principle. This trial is registered with the ISRCTN registry, number ISRCTN07336477. Findings: Between March 18, 2011, and Dec 9, 2013, we randomly assigned 144 women, 72 to each group. Primary outcome data were available for 62–64 (86–89%) VFT and 67–68 (93–94%) PMR participants. There were no group differences in child outcome (cognitive development, adjusted difference −1·01 [95% CI −5·11 to 3·09], p=0·63; language development, 1·33 [–4·16 to 6·82], p=0·63; behaviour problems, −1·77 [–4·39 to 0·85], p=0·19; attachment security, 0·02 [–0·06 to 0·10], p=0·58), with both groups achieving scores similar to non-clinical norms on all outcomes. There were six serious adverse events: five in the VFT group (in two participants) and one in the PMR group. None was treatment-related. Interpretation: The effect of persistent postnatal depression on children is a major public health issue. For both treatment groups there was sustained remission from depression, and child development outcomes were in the normal range. The precise mechanisms accounting for the observed positive child outcomes cannot be ascertained from this study. Funding: Wellcome Trust.